Low Molecular Weight Heparin Administered once versus twice Daily in Patients with Venous Thromboembolism - Couturaud, Francis; Julian, Jim A.; Kearon, Clive (Thrombosis and Haemostasis, 2001)
Background. Low molecular weight heparin is as effective and safe as unfractionated heparin for treatment of acute venous thromboembolism. It is uncertain whether low molecular weight heparin should be administered once-daily or twice-daily in this setting. Method. A meta-analysis of randomized studies which directly compared once- and twice-daily administration of low molecular weight heparin for the treatment of acute venous thromboembolism was performed. A literature search was performed using Advanced Pub Med and the Cochrane library database, and abstracts from recent meetings were reviewed. Two investigators extracted data independently. Results. Five studies, involving 1522 patients, were eligible. There were no statistically significant differences in the frequencies of symptomatic (odds ratio, 0.85 in favor of once-daily therapy at three months, p = 0.6), and asymptomatic, recurrent venous thromboembolism; total and major bleeds (odds ratio, 1.16 in favor of twice-daily therapy at 10 days, p = 0.8); and death, at 10 days, as well as at three months of follow-up. Conclusion. Once- daily low molecular weight heparin appears to be as effective and safe as twice-daily administration for the acute treatment of venous thromboembolism. However, there is inadequate data from studies that directly compared once-daily and twice-daily administration to be able to exclude the possibility of a higher frequency of fatal bleeding with once-daily therapy.
Keywords: Low molecular weight heparin; venous thrombosis; meta-analysis